Modifikasi Kulit Telur Ayam Dan Fly Ash Sebagai Katalis Untuk Reaksi Transesterifkasi Minyak Sawit Off Grade Menjadi Biodiesel - Putra, Yogi Lesmana; Helwani, Zuchra; Saputra, Edy (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Eggshells modificated of solid base catalyst through calcination, hydration, dehydration methods with fly ash through impregnation method to load calcium oxide with eggshells as precursor. Effect of dehydration temperature and time on the catalytic performance were studied. The catalyst with the highest activity is obtained when the dehydration temperature of 600 °C and the dehydration time of 3 hours with transesterification reaction conditions of a molar ratio of methanol/oil 6:1, catalyst dosage of 6% by weight, temperature of 70 °C for 2 hours with yield biodiesel results reached 84,32%.Keywords: biodiesel, calcination, calcium oxide, catalysts, dehydration, fly ash, hydration, impregnation, transesterification.